Avaliação das condições de processo na resistência da levedura ao teor final de etanol na fermentação alcoólica - Cruz, Mariana Lopes (2015)
The increase in energy consumption, depletion of fossil fuels and growing concerns about the environment have become strong justifications for energy generation applied to the use of biofuels. In expanding production of bioethanol by Brazilian plants, the incorporation of innovative processes and technological development have had a key role, with increased production efficiency and progressive reduction of environmental impacts and agricultural economy, especially with regard to reducing the volume of stillage, a byproduct of ethanol production. In this work was studied the yeast Saccharomyces cerevisiae Y904 resistance in alcoholic fermentation process operating in fed batch reactor by analyzing the effect of the reactor feeding time, temperature, concentration of inoculum and substrate on fermentation yield, productivity and concentration residual reducing sugars. Assays were carried out in a mini fermentor using a synthetic medium sucrose-based and yeast extract. The sugar and ethanol concentrations were determined by liquid chromatography (HPLC), and cell concentrations were determined by spectrophotometric method. Through a statistical analysis in Statistica 7.0 software was possible to determine the tracks that maximized the variables in the factorial experimental design and the Central Composed Design. As a result, it was found that the maximum concentration at which ethanol production thereof was completely inhibited (P\'max) was 137 g/L obtained at 25 °C. It was observed that using the condition that maximizes generated at the CCD variables, temperature 26 °C, 5 hours filling, 240 g/L concentration of ART and 35 g/L of inoculum concentration was obtained a value productivity of 6.0 g /Lh, 93% yield and 14.4 °GL in 10 hours of incubation, indicating that the optimization equations given and managed by the CCD describe the behavior of the fermentation process. With the yeast adapted at 4 °C, were obtained low time of fermentation and using sugarcane juice as the substrate using the same adapted yeast led to higher yields (94%) and productivity (10.1 g/L.h) when using the inoculum pH 2.5. Alcoholic fermentation using Saccharomyces cerevisiae yeast fed-batch reactor provided greater productivity and income when compared to data reported in the literature in which they used the same conditions studied in this work.